The effect of copper acetate on hepatocyte metabolism in vitro - I. S. Trukhan; N. N. Dremina; I. A. Shurygina (Acta Biomedica Scientifica, 2024)
Background. Copper ions are necessary for maintaining basic physiological processes in the mammalian organism. However, their excessive absorption or accumulation in cells can lead to the development or exacerbation of various pathological processes. The  cytotoxic and  genotoxic effects of  high concentrations of  copper compounds are  currently well studied in  various cell cultures, whereas the  effect of non-toxic amounts of copper ions on physiological processes in cells, including during their cultivation, has been extremely poorly studied.The aim of the study. To investigate the effect of copper ions on changes in the intracellular amount of mitochondrial cytochrome C oxidase and glutathione synthetase.Materials and methods. A primary culture of hepatocytes was obtained, which was exposed to copper acetate at a concentration of 200 µg/ml in terms of copper content for 24 hours. After fixation, the samples were stained immunocytochemically using antibodies to  cytochrome  C oxidase (CcO) subunit  I and  glutathione synthetase (GS).Results. In  hepatocyte culture, a  significant increase in  the  intensity of  fluorescent staining of the two analyzed enzymes was demonstrated both after 6 hours and  after  24  hours of  exposure to  copper ions, which indicates a  change in  their number in  cells. At  the  same time, the  increase in  the  amount of  CcO was more intense in the first 6 hours of incubation with a microelement, whereas in the next 18 hours, changes in the intracellular content of CcO were less pronounced. The increase in the intensity of the GS fluorescent stain was more active and was observed throughout the entire cultivation period.Conclusion. From the  results obtained, it  can  be concluded that copper ions in  non-toxic concentrations are  able to  influence key indicators of  cell viability in culture by changing the amount of one of the main energy metabolism enzymes and the enzyme that provides synthesis of the most important low-molecular antioxidant glutathione.